Variscan and Alpine structure of the hills of Barcelona: geology in an urban area - P. Santanach, P.; Casas, J. M.; Gratacós, O.; Sàbat, F.; Liesa, M.; Muñoz, J. A.; Sàbat, F. (Journal of Iberian Geology, 2011)
Line 9 of the underground railway is currently being constructed in Barcelona. This undertaking necessitates tunnelling through a number of hills that are mainly made up of Paleozoic rocks, which exhibit a complex structure due to the superposition of Variscan, Mesozoic, Paleogene and Neogene structures. We present a 1:5000 scale map of the hills of Barcelona. Unpublished field notes from surveys carried out in the 1940s and in the early 1970s were crucial for drawing up this detailed map, which together with subsurface data from public works and our study of the few remaining outcrops, enabled us to provide fresh insights into the structure of this area. We also discuss the age of the structures on the basis of cross-cutting relationships and regional considerations. Our conclusions highlight the ongoing need for a geological survey of cities given that our understanding of their geology depends on impermanent outcrops and on the recovery of lost subsurface data. These considerations call for a suitable management of the geological information in urban areas with a complex geology for planning and developing safe infrastructures.